2016
DOI: 10.1007/s11012-016-0495-y
|View full text |Cite
|
Sign up to set email alerts
|

On the impulsive dynamics of T3 tensegrity chains

Abstract: Taking the cue from two recent papers,\ud Fraternali et al. (J Mech Phys Solids 60:1137–1144,\ud 2012), and Fraternali et al. (Appl Phys Lett 105:201903,\ud 2014), we sample numerically the impulsive dynamics\ud of chains consisting of T3 tensegrity modules. We\ud concentrate on illustrating the effects of the kinetic\ud coupling between axial strain and twist, a distinguishing\ud feature of T3 modules that was switched off in the cited\ud papers; in addition, we demonstrate by examples that\ud another feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…Ordinary engineering materials typically exhibit either elastic stiffening (e.g., crystalline solids) or elastic softening (e.g., foams). More puzzling is the geometrically nonlinear response of structural lattices based on tensegrity units (e.g., tensegrity prisms), which may gradually change their elastic response from stiffening to softening through the modification of mechanical, geometrical, and prestress variables (tensegrity metamaterials (Skelton and de Oliveira, 2010;Fraternali et al, 2012Fraternali et al, , 2014Fraternali et al, , 2015aAmendola et al, 2014;Davini et al, 2016;Rimoli and Pal, 2017)). Tensegrity structures are prestressable truss structures, which are obtained by connecting compressive members (bars or struts) through the use of pre-stretched tensile elements (cables or strings).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary engineering materials typically exhibit either elastic stiffening (e.g., crystalline solids) or elastic softening (e.g., foams). More puzzling is the geometrically nonlinear response of structural lattices based on tensegrity units (e.g., tensegrity prisms), which may gradually change their elastic response from stiffening to softening through the modification of mechanical, geometrical, and prestress variables (tensegrity metamaterials (Skelton and de Oliveira, 2010;Fraternali et al, 2012Fraternali et al, , 2014Fraternali et al, , 2015aAmendola et al, 2014;Davini et al, 2016;Rimoli and Pal, 2017)). Tensegrity structures are prestressable truss structures, which are obtained by connecting compressive members (bars or struts) through the use of pre-stretched tensile elements (cables or strings).…”
Section: Introductionmentioning
confidence: 99%
“…Tensegrity structures are prestressable truss structures, which are obtained by connecting compressive members (bars or struts) through the use of pre-stretched tensile elements (cables or strings). Several studies have shown that it is possible to modulate the properties of tensegrity units by playing with local (or internal) and global (or external) prestress variables, so as to match arbitrary, user-defined nonlinear constitutive laws at the mesoscale, such as, e.g., power-law responses with arbitrary exponents (refer, e.g., to Skelton and de Oliveira (2010); Fraternali et al (2012Fraternali et al ( , 2014Fraternali et al ( , 2015a; Amendola et al (2014); Davini et al (2016); Rimoli and Pal (2017) and references therein). For what concerns the wave dynamics of tensegrity metamaterials, it has been shown that elastically hardening systems support compressive solitary waves and the unusual reflection of waves on material interfaces (Fraternali et al, 2012;Davini et al, 2016), while elastically softening systems support the propagation of rarefaction solitary waves under initially compressive impact loading Fraternali et al, 2014Fraternali et al, , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…[22]. We show that our 3D modeling of tensegrity columns allows us to detect different strain wave profiles, as a function of the applied prestress, and a rigidity parameter describing the kinematics of the terminal bases.…”
Section: Introductionmentioning
confidence: 84%
“…We compare the dynamics of columns composed of prisms with flexible bases (hereafter referred to as FB-columns) with that of columns composed of prisms equipped with rigid bases (RB-columns). The analyzed columns have the same geometric and mass data of those analized in [22]. We consider tensegrity columns subject to a state of prestress in the reference configuration, which is obtained by applying a prestrain p = 0.002 to the cross cables.…”
Section: Wave Dynamics Of Tensegrity Columnsmentioning
confidence: 99%
“…[20] and [23]. An additive manufacturing (AM) technique based on Electron Beam Melting (EBM) is employed to build all the elements of the tested structure, except for the cables, which are subsequently added to the 3d-printed structure through a post-tensioning technique [18].…”
Section: Introductionmentioning
confidence: 99%